PENTINGNYA KLINIK KONSULTASI UMKM BIDANG FOTO DAN VIDEO PRODUK, KERJASAMA ANTARA INSTITUT STIAMI DENGAN UMKM DKI JAKARTA SERTA JAKPRENEUR, NOVEMBER – DESEMBER 2021 - Agoestyowati, Redjeki (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2022)
We have already known that due to the COVID-19 pandemic, many employees or workers have lost their jobs or been laid off at a productive age. With this background, the DKI Jakarta Department of Industry, Trade, Cooperatives, Small and Medium Enterprises (PPKUKM) collaborates with the STIAMI Institute of Social Sciences and Management to provide assistance to SMEs fostered by DKI Jakarta or Jakpreneur, in various fields, and one of them is about making product photos or videos with the aim of increasing sales. This community service activity is called a Consultation Clinic, was carried out boldly during November and December 2021, and consultations were continued via Whatsapp. This was well received by the participants because the material presented was quite simple and easy, so they could immediately apply photo or video products with their existing mobile camera. Participants feel the benefits of this Abdimas activity and they are interested in continuing to work on making product photos and videos.